Analytical Study – Strategic Operation and Leadership Engagement in M&A in Different Sectors Across US, UK, and APAC Region - Thakur, Vijay Kumar (Digital Repository of Theses, 2025)
Mergers and Acquisitions (M&A) are crucial for business development and market cycles globally. This study aims to understand the necessity, implications, and impact of M&A on both acquiring and acquired companies. It covers various sectors, including banking, IT, energy, and oil, analyzing data from multiple countries such as the UK, US, Russia, India, China, Japan, and Sri Lanka. The research identifies primary drivers for M&A, such as higher cash flow, economies of scale, and growth opportunities. It examines the implications of M&A on tax laws, policies, and socio-economic changes. Human capital-centric strategies and management decisions are highlighted as crucial for successful M&A. The research discusses the impact of external factors such as global economic conditions, geopolitical situations, and the COVID-19 pandemic on M&A activities. The methodology applied in this study uses secondary dataset that were analyzed using statistical methods for the quantitative data and thematic analysis for the qualitative data. The study emphasizes the need for appropriate strategies to manage human capital and business operations effectively. Issues related to tax evasion and the legal aspects of M&A are addressed, suggesting the need for robust accounting standards and forensic accounting to detect and prevent irregularities. The findings of this research indicate that digital transformation significantly enhances organizational efficiency by streamlining processes and reducing operational costs. Additionally, the study reveals that digital transformation positively impacts employee productivity by providing better tools and resources, fostering a more collaborative work environment, and enabling remote work. However, the research also highlights challenges such as the need for continuous training and the potential for increased work-related stress due to constant technological changes. Sector-specific insights into M&A activities in the banking sector in India, Pakistan, and Nigeria, and the oil market in Russia are provided. The study concludes with recommendations for future research and strategies for successful M&A, considering the impact of technological advancements and external factors to maximize their benefits while mitigating potential drawbacks. The study provides valuable insights for organizations seeking to navigate the complexities of digital transformation and improve their overall performance.